How Intermediate Cities Localise the Sustainable Development Goals through Sustainable Mobility Planning - Calabro, Grazia; Carlucci, Fabio; D’Alessandro, Carlotta; Trincone, Barbara (European Scientific Journal, ESJ, 2026)
The implementation of the Sustainable Development Goals (SDGs) continues to be constrained by a persistent gap between globally defined objectives and their effective translation into local development processes. This challenge is particularly relevant for intermediate cities, which occupy a strategic position between metropolitan centres and peripheral territories and therefore play a crucial role in connecting global sustainability agendas with place-based policy implementation. This paper investigates how intermediate cities localise SDG objectives through sustainable mobility planning instruments operating within multi-level governance systems. Building on a policy analysis supported by illustrative case studies, the paper investigates this research question. The findings suggest that Sustainable Urban Mobility Plans (SUMPs) and related mobility planning instruments operate as effective governance mechanisms for translating global sustainability objectives into territorially embedded policies and actions. Through the integration of transport planning, accessibility policies, environmental objectives, and stakeholder participation, these instruments contribute to the implementation of several SDGs, particularly SDG 11 (Sustainable Cities and Communities), SDG 13 (Climate Action), SDG 9 (Industry, Innovation and Infrastructure), and SDG 10 (Reduced Inequalities). The analysis further shows that successful SDG localisation depends on three interrelated conditions: effective coordination across governance levels, integration between mobility and territorial planning, and the adoption of monitoring frameworks based on measurable indicators. The paper argues that intermediate cities should not be regarded merely as recipients of sustainability policies but as active governance arenas in which global objectives can be operationalised through integrated mobility planning. In this perspective, mobility planning instruments become key policy tools for strengthening territorial cohesion, institutional coordination, and the local implementation of the 2030 Agenda.